ANALISIS SOSIAL EKONOMI DAN PEMASARAN PERIKANAN LAUT DI KELURAHAN BELAWAN I KOTA MEDAN - Muhammad Thamrin (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThe results showed that the value of the coefficient of determination R-square 0.93, can be interpreted that the simultaneous possession of fishing gear status factors, capital, work ethic and marketing types mentioned above were able to explain changes in fishing revenues 93%. Partially work ethic and marketing factors significantly affect the value t count> t table. While the status of the fishing gear and ownership of capital does not significantly affect the value of t calculated <t table against the income of fishermen in the 95% confidence level (a = 5%).Key words: marketing,  income of fishermen